Erratum: Anker A. (2011) “Six new species and three new records of infaunal alpheid shrimps from the genera Leptalpheus Williams, 1965 and Fenneralpheus Felder & Manning, 1986 (Crustacea, Decapoda)”. Zootaxa, 3041, 1–38. - Anker, A. (Zootaxa, 2012)
(Erratum)